Raspberry Pi Cookbook - Simon Monk (O'Reilly Media / Shroff Publishers & Distributers, 2016)
With millions of new users and several new models, the Raspberry Pi ecosystem continues to expand-along with a lot of new questions about the Pi's capabilities. The second edition of this popular cookbook provides more than 240 hands-on recipes for running this tiny low-cost computer with Linux, programming it with Python, and hooking up sensors, motors, and other hardware-including Arduino and the Internet of Things. Prolific hacker and author Simon Monk also teaches basic principles to help you use new technologies with Raspberry Pi as its ecosystem continues to develop. This cookbook is ideal for programmers and hobbyists familiar with the Pi through resources, including Getting Started with Raspberry Pi (O'Reilly). Python and other code examples from the book are available on GitHub. Set up your Raspberry Pi and connect to a network Work with its Linux-based operating system Program Raspberry Pi with Python Give your Pi "eyes" with computer vision Control hardware through the GPIO connector Use Raspberry Pi to run different types of motors Work with switches, keypads, and other digital inputs Use sensors to measure temperature, light, and distance Connect to IoT devices in various ways Create dynamic projects with Arduino